Distribution related to temperature and salinity of the shrimps Acetes americanus and Peisos petrunkevitchi (Crustacea: Sergestoidea) in the south-eastern Brazilian littoral zone - Simães, Sabrina Morilhas [UNESP]; Castilho, Antonio Leão [UNESP]; Fransozo, Adilson [UNESP]; Negreiros-Fransozo, Maria Lúcia [UNESP]; Da Costa, Rogerio Caetano (Cambridge University Press (CUP), 2013)
The abundance and ecological distribution of Acetes americanus and Peisos petrunkevitchi were investigated from July 2006 to June 2007, in Ubatuba, Brazil. Eight transects were identified and sampled monthly: six of these transects were located in Ubatuba bay, with depths reaching 21 m, and the other two transects were in estuarine environments. A total of 33,888 A. americanus shrimp were captured, with the majority coming from the shallower transects (up to 10 m). Conversely, 6,173 of the P. petrunkevitchi shrimps were captured in deeper areas (from 9 to 21 m). No individuals from either species were found in the estuary. The highest abundances obtained for both species were sampled during the summer. Canonical correlation analysis resulted in a coefficient value of 0.68 (P = 0.00). The abundance of both species was strongly correlated with depth. Variations in temperature and salinity values were also informative in predicting the seasonal presence of P. petrunkevitchi in deeper areas and A. americanus in the shallower areas of the bay. It is conceivable that the shrimp adjust their ecological distribution according to their intrinsic physiological limitations. © 2012 Marine Biological Association of the United Kingdom.
Keywords: abundance; pelagic shrimp; spatio-temporal distribution; canonical analysis; crustacean; estuarine environment; intertidal environment; pelagic environment; physiological response; salinity; spatial distribution; temperature effect; temporal variation; Brazil; Sao Paulo [Brazil]; Ubatuba